Deterioration of RC beams due to reinforcement corrosion - Gupta, Anuj (My University, 2013)
Reinforced concrete structures have not been immune to the ravages of corrosion despite the protection that concrete provides to embedded steel. Since steel corrosion remains unnoticed inside the concrete, it further accelerates and can cause loss of life and property. This report discusses the results on deterioration caused to reinforced beams due to corrosion at different levels. Five RC beams (127 x 227 x 4100) mm were casted, four of which were corroded to different levels i.e. (6days, 12days,18days & 28days) by impressed current technique, while one remain as control beam. All four beams were visually inspected at the end of their respective corrosion period for the extent of damage in the RC beams, with the increase in age of corrosion. Each beam was tested under static four-point loading and corresponding loads and deflections were recorded. The results of this experiment clearly show that there is a decrease in load carrying capacity, deflection capacity and stiffness with the increase in age of corrosion. Most importantly it was noticed that as corrosion increased the failure mode of beams shifts from predictable ductile failure to brittle failure. After the destructive testing, reinforcement was retrieved from the beams by dismantling and then cleaned to find the mass loss. The results show that there was an increase in mass loss in the reinforcement with the increase in corrosion level. After the beam tests, bars were tested using non-destructive technique. The method used was ultrasonic testing of bars in air to detect the damages in the bars at different corrosion levels. Two ultrasonic techniques of pulse transmission and pulse echo were used to monitor the healthy and damaged bars. The signals obtained from ultrasonic testing of bars shows decrease in amplitude voltage with increasing in corrosion level, which clearly relates to the state of bars i.e. as the flaws in the bars increases amplitude signal drops. From ultrasonic test results it was also noticed that this technique is sensitive to even small damages in the bars which is of great importance.
Master of Engineering (Structures), Thesis
Keywords: Corrosion; reinforcement; ultrasonic; Load Deflection; chloride